14C and 10Be dated Late Holocene fluctuations of Patagonian glaciers in Torres del Paine (Chile, 51°S) and connections to Antarctic climate change - Garcia, Juan-Luis; Hall, Brenda L.; Kaplan, Michael R.; Gomez, Gabriel A.; De Pol Holz, Ricardo Hernán; Garcia, Victor J.; Schaefer, Joerg M.; Schwartz, Roseanne (My University, 2020)
Southern Hemisphere Holocene glacier chronologies are important for unraveling past climate change, mid-to-high latitude teleconnections, and regional to global climate forcing. At present, a significant number of glacier chronologies for Patagonia are based on C-14 dating, which may afford only maximum or minimum-limiting dates. Here, we combine geomorphology and stratigraphy with radiocarbon (C-14) and beryllium-10 (Be-10) surface exposure-age dating at three outlet glaciers, Zapata, Tyndall, and Pingo. These glaciers drain the southernmost tip of the Southern Patagonian Ice Field at Torres del Paine National Park, Chile (51 degrees S). After an expansion that we date at 3200 yr. B.P., the Torres del Paine glaciers expanded to their last major Late Holocene maxima at 600 and 340 yr. B.P., with the final dated readvance after 190 yr. B.P. We use these data, together with other Patagonian glacier records, to define the early, mid and final glacial stages of the last millennium. These cold events were separated by warm conditions that allowed the Nothofagus forest to colonize deglaciated land. The presence of nearconcurrent glacier fluctuations in Patagonia and Antarctic Peninsula indicates widespread cooling punctuated the Late Holocene, including the last millennium, across much of the extratropical Southern Hemisphere. We link this cooling to cold oceanographic-atmospheric conditions forced by a northern shift or intensification of the Southern Westerly Winds. Such scenario increased northward advection of cold Antarctic circumpolar water along western Patagonia and favored decreased upwelling of warm circumpolar deep water together with expanded sea ice around the Antarctic Peninsula. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: torres del paine; patagonian glaciers; southern westerly winds; holocene; antarctic peninsula; radiocarbon and be-10 cosmogenic dating